2021
DOI: 10.1172/jci.insight.153175
|View full text |Cite
|
Sign up to set email alerts
|

NK and CD8+ T cell phenotypes predict onset and control of CMV viremia after kidney transplant

Abstract: Cytomegalovirus (CMV) causes mostly asymptomatic but lifelong infection. Primary infection or reactivation in immunocompromised individuals can be life-threatening. CMV viremia often occurs in solid organ transplant (SOT) recipients and associates with decreased graft survival and higher mortality. Furthering understanding of impaired immunity allowing CMV reactivation is critical to guiding anti-viral therapy and examining CMV's impact on outcomes of SOT. This study characterized longitudinal immune responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 67 publications
2
9
0
Order By: Relevance
“…Further analysis of IL-12 concentrations in the plasma of kidney transplant patients with reported NK cell expansion showed evidence for a long-term increase of the IL-12p40/IL-12p70 ratio in CMV PCR+ individuals, suggesting a contribution of these low IL-12 levels to NK cell expansion (Fig. 1 A; Pickering et al, 2021;Piazzolla et al, 2001;Ethuin et al, 2003). Consequently, we evaluated the efficacy of IL-12 to mediate human NK cell expansion directly by ex vivo stimulation of NK92 cells or purified primary NK cells with titrated amounts of IL-12 (Romee et al, 2012).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Further analysis of IL-12 concentrations in the plasma of kidney transplant patients with reported NK cell expansion showed evidence for a long-term increase of the IL-12p40/IL-12p70 ratio in CMV PCR+ individuals, suggesting a contribution of these low IL-12 levels to NK cell expansion (Fig. 1 A; Pickering et al, 2021;Piazzolla et al, 2001;Ethuin et al, 2003). Consequently, we evaluated the efficacy of IL-12 to mediate human NK cell expansion directly by ex vivo stimulation of NK92 cells or purified primary NK cells with titrated amounts of IL-12 (Romee et al, 2012).…”
Section: Resultsmentioning
confidence: 95%
“…Low IL-12 concentrations lead to human primary NK cell activation without expansion Our objective was to evaluate the ability of IL-12 to mediate human NK cell proliferation and expansion since IL-12 is essential for mouse NK cell expansion and memory NK cell generation during MCMV infection (Sun et al, 2012). In line with the mouse model, phenotypic changes in human NK cells are associated with human CMV (HCMV) infection and elevated IL-15 levels in vivo (Pickering et al, 2021). Further analysis of IL-12 concentrations in the plasma of kidney transplant patients with reported NK cell expansion showed evidence for a long-term increase of the IL-12p40/IL-12p70 ratio in CMV PCR+ individuals, suggesting a contribution of these low IL-12 levels to NK cell expansion (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a recent study by Pickering et al . 14 found that NK cells and CD8 + T cells play an important role in the process of CMV infection in patients after renal transplantation and NK cells are closely related to the development of CMV infection while CD8 + T cells are essential for the control of CMV. Their results were consistent with our findings.…”
Section: Discussionmentioning
confidence: 98%
“…These conclusions are consistent with our research, as we found that the NK cell count, immunoglobulin G and the CD8 + CD28 + T-cell count in active CMV-infected patients with sepsis were significantly higher than in those without active CMV infection. In addition, a recent study by Pickering et al 14 found that NK cells and CD8 + T cells play an important role in the process of CMV infection in patients after renal transplantation and NK cells are closely related to the development of CMV infection while CD8 + T cells are essential for the control of CMV. Their results were consistent with our findings.…”
Section: Discussionmentioning
confidence: 99%